Comparison Between Photoselective Vaporization of Prostate by Diode Laser and Monopolar Transurethral Resection of Prostate in Single Center Experience - Zaid Ali Abdul Hussein1, Ali Hamdan Fahad2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Transurethral resection of prostate has been regarded as the gold standard surgical management of benign prostatic hyperplasia (BPH).With the evolution of new technologies, laser prostatectomy emerged as an alternative.Aim of the study: To compare the rate of outcome of diode laser vaporization of prostate and Transurethral Resection of Prostate in Al Diwaniya governorate.Patients and Method: From October 2017 to October 2018, forty patients with surgical indications of prostatectomy were enrolled in this study. Their ages ranged from 60-75 years with a mean age 68.6 years and prostate size ranged from 40-80 ml with a mean size 62.175 ml. Twenty patients underwent diode laser vaporization of prostate and another 20 patients underwent Transurethral Resection of Prostate. The choice based on surgeon preference and patient ability. Preoperative evaluation was done for all patients by history, physical examination and investigations. International Prostate Symptoms Score, maximum flow rate, digital rectal examination, prostate specific antigen, abdominal ultrasound, urinalysis, blood urea, s.creatinine, complete blood count were all done preoperatively. One pint of compatible fresh blood prepared.Results: The rate of significant bleeding and transfusion in diode PVP and TURP was (zero vs. 35% respectively), in PVP and TURP the mean irrigation amount perioperatively was (10.10 vs. 33.15 pints respectively), mean operative time was (70.80 vs. 50.00 min respectively) ,mean hospital stay was (16.03 vs. 30.09 hours respectively), mean time to urethral catheter removal was (24 vs. 81.71 hours respectively), postoperative complication rate (mainly dysuria) was (75% vs. 65% respectively), mean postoperative IPSS was (14.40 vs. 14.20 respectively) , mean postoperative Qmax was (15.45 vs. 16.30 ml/sec respectively ). There was no statistical difference between both groups in regard to lowering IPSS or increment in Qmax. The mean cost was (1500 vs. 500.42 dollars) in diode PVP and TURP respectively.Conclusion: Diode laser vaporization of prostate is a good alternative to TURP with comparable results in treatment of BPH especially in patients taking anticoagulant drugs who cannot stop their medication. However, the high cost of this procedure and dysuria as a complication may prevent the common use of this technique.